Cyprus Research Award – “Young Researcher” 2015 - Stephanou, Pavlos S. (My University, 2026)
I received the Cyprus Research Award – “Young Researcher” 2015 in the Thematic Area: Physical Sciences and Engineering.
Keywords: Sciences